Effect of Repeated Earthquakes on the School Building in Northern Sumatra - Ade Faisal, Ph.D (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
The earthquakes struck a region near the active fault for many times. The yielded structures after an earthquake might become excessive damages after experiencing another earthquake. The concept of seismic design of building has not consider this type of hazard. Recent studies indicate that the effect of repeated earthquake is significantly occurred on the moment resisting bare frames, either made from steel or concrete material. This paper investigates the effect of repeated earthquake on the frames with infilled brick wall. The frames represent school building built on the regions near the Sumatran active fault, Indonesia. The result shows that the sequence of plastic hinges occur on the structures model after experiencing the repeated earthquake. It starts from the brick wall and then spreads to the columns and beams. For the single earthquakes, the brick wall of structures model tends to perform damage, but few of columns and beams experiences hinges. These conclude that the future repeated earthquake can not be underestimated.